An eye-tracking investigation of written sarcasm comprehension: the roles of familiarity and context - Turcan, Alexandra; Filik, Ruth (American Psychological Association, 2016)
This paper addresses a current theoretical debate between the standard pragmatic model, the graded salience hypothesis, and the implicit display theory, by investigating the roles of the context and of the properties of the sarcastic utterance itself in the comprehension of a sarcastic remark. Two eye-tracking experiments were conducted where we manipulated the speaker’s expectation in the context and the familiarity of the sarcastic remark. The results of the first eye-tracking study showed that literal comments were read faster than unfamiliar sarcastic comments, regardless of whether an explicit expectation was present in the context. The results of the second eye-tracking study indicated an early processing difficulty for unfamiliar sarcastic comments, but not for familiar sarcastic comments. Later reading time measures indicated a general difficulty for sarcastic comments. Overall, results seem to suggest that the familiarity of the utterance does indeed affect the time-course of sarcasm processing (supporting the graded salience hypothesis), while there is no evidence that making the speaker’s expectation explicit in the context affects it as well (thus failing to support the implicit display theory).